Hak Anak Dalam Perspektif Islam - Syaidah, Khasnah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
The children are not miniature of the man. They have own world with all special characteristics. They have numerous potencies. These potencies must be developed with education. Without understanding about them, the parents can not give the best experient. The parents can recognize them with education. Today, there is phenomenon that government and social foundation commit to effort in the direction of humanizing children toward liberating them from transgression and oppression, for example: trafficking, seduction, drug, etc. This article wants to discuss the children's rights for life in Islamic perspective.